Трехсуточная динамика метеоэлементов при пылевых бурях Приаралья - Тлеумуратова, Б.С; Уразымбетова, Э.П; Султашов, Р.Г (SCIENCE and SOCIETY, 2023)
This article provides a statistical analysis of the three-day dynamics of meteorological elements (air temperature and humidity, atmospheric pressure, wind speed) in order to identify meteorological patterns of salt and dust storms on the dried bottom of the Aral Sea. The daily dynamics of these 4 meteorological elements is considered separately, as the first stage of the necessary research to predict salt and dust storms. The difference is determined between the standard data of meteorological stations a day before and during a dust storm is calculated, and then the distribution series of these differences. The same procedure is performed for posterior weather conditions. In order to identify is also calculated the characteristic values of meteorological elements during a dust storm, their distribu- tion function Mathematical expectation were calculated series of distributions for all indicators. The methods of statistical and synoptic analysis, the method of analogies, were used to identify long-term data of standard meteorological measurements of the Aral weather stations, synoptic maps and images from an artificial Earth satellite.
Keywords: Aral crisis; dust storm; salt removal; meteorological elements; statistical analysis